Morphological, physiological and bio-chemical characterization of amaranth (Amaranthus spp.) genotypes - Nikita Mahto; Bineeta Michael Bara (Annals of Agricultural Research, 2026)
The Present investigation was carried out with 12 amaranth genotypes including two check variety (Pusa Kirti and Pusa Kiran) during Rabi 2022-2023 in RBD with three replications at Field Experimentation Centre, Department of Genetic and Plant Breeding, Naini Agriculture Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, (U.P.), to evaluate Amaranth (Amaranthus spp.) genotypes for Morphological, Physiological and Bio-Chemical parameters. Analysis of variance showed highly significant differences among 12 Amaranth genotypes for 13 Morphological, 2 Physiological and 2 Bio- Chemical characteristics. Genotype IC-35578 was identified as the best genotype for 7 Morphological and 2 Physiological characters, and genotype IC-35583 was identified as the best genotype for 9 Morphological and 2 Bio-Chemical characters.